Development Of Tourism Villages With The Application Of Simple Accounting To Business Actors In Pematang Serai Village, Langkat District - Nur Aliah; Miftha Rizkina (Universitas 17 Agustus 1945 Semarang, 2023)
This study aims to determine the application of simple accounting carried out by the Pematangs erai tourism village community who have a business. This research approach with qualitative descriptive method. The sample of this research is a business actor in the village of Pematang Serai which is as many as 8 business actors. The data analysis technique used is direct observation using interviews and documentation. The results of this study are Pematang serai is a village in langkat district that has potential in the development of village tourism, the development of this tourist village is supported by the langkat government, people who have a business in the village have not applied simple accounting records.